Ventromedial hypothalamic nucleus subset stimulates tissue thermogenesis via preoptic area outputs - Rashmita Basu; Andrew J. Elmendorf; Betty Lorentz; Connor A. Mahler; Olivia Lazzaro; Britany App; Shudi Zhou; Yura Yamamoto; Mya Suber; Jamie C. Wann; Hyun Cheol Roh; Patrick L. Sheets; et al. (Elsevier, 2024)
Objective: Hypothalamic signals potently stimulate energy expenditure by engaging peripheral mechanisms to restore energy homeostasis. Previous studies have identified several critical hypothalamic sites (e.g. preoptic area (POA) and ventromedial hypothalamic nucleus (VMN)) that could be part of an interconnected neurocircuit that controls tissue thermogenesis and essential for body weight control. However, the key neurocircuit that can stimulate energy expenditure has not yet been established. Methods: Here, we investigated the downstream mechanisms by which VMN neurons stimulate adipose tissue thermogenesis. We manipulated subsets of VMN neurons acutely as well as chronically and studied its effect on tissue thermogenesis and body weight control, using Sf1Cre and Adcyap1Cre mice and measured physiological parameters under both high-fat diet and standard chow diet conditions. To determine the node efferent to these VMN neurons, that is involved in modulating energy expenditure, we employed electrophysiology and optogenetics experiments combined with measurements using tissue-implantable temperature microchips. Results: Activation of the VMN neurons that express the steroidogenic factor 1 (Sf1; VMNSf1 neurons) reduced body weight, adiposity and increased energy expenditure in diet-induced obese mice. This function is likely mediated, at least in part, by the release of the pituitary adenylate cyclase-activating polypeptide (PACAP; encoded by the Adcyap1 gene) by the VMN neurons, since we previously demonstrated that PACAP, at the VMN, plays a key role in energy expenditure control. Thus, we then shifted focus to the subpopulation of VMNSf1 neurons that contain the neuropeptide PACAP (VMNPACAP neurons). Since the VMN neurons do not directly project to the peripheral tissues, we traced the location of the VMNPACAP neurons' efferents. We identified that VMNPACAP neurons project to and activate neurons in the caudal regions of the POA whereby these projections stimulate tissue thermogenesis in brown and beige adipose tissue. We demonstrated that selective activation of caudal POA projections from VMNPACAP neurons induces tissue thermogenesis, most potently in negative energy balance and activating these projections lead to some similar, but mostly unique, patterns of gene expression in brown and beige tissue. Finally, we demonstrated that the activation of the VMNPACAP neurons' efferents that lie at the caudal POA are necessary for inducing tissue thermogenesis in brown and beige adipose tissue. Conclusions: These data indicate that VMNPACAP connections with the caudal POA neurons impact adipose tissue function and are important for induction of tissue thermogenesis. Our data suggests that the VMNPACAP → caudal POA neurocircuit and its components are critical for controlling energy balance by activating energy expenditure and body weight control.